EVALUASI KEBIJAKAN PENGEMBANGAN OBJEK WISATA PEMANDIAN ALAM BANYU BIRU DALAM MENINGKATKAN EKONOMI MASYARAKAT LOKAL - Taufiq Soeltanto; Nurul Laila; Yuni Hartono (JOURNAL AKSES STIA MALANG, 2023)
Natural bathing tourism objects are one of the significant potentials in the development of tourism in an area.The purpose of this study is to evaluate the policy of developing Banyu Biru natural bathing tourism objects andtheir impact on improving the economy of local communities. This research uses qualitative and quantitativeanalysis methods by collecting data through surveys, interviews, and field observations. The results showed thatthe policy of developing Banyu Biru natural bathing tourism objects has been running quite well in terms of itspositive impacts, namely: in the form of physical buildings, resources and local economic conditions that increase every year, but there are several impacts that make its implementation still not optimal, especially in theuse of attraction stages, road security to Banyu Biru natural bathing tourism and no public transportation to thetourist attraction. Based on the results of the policy evaluation of the development of Banyu Biru natural bathingtourist attraction, it can be concluded that this policy has succeeded in improving the economy of the local community through increasing the number of tourists, increasing income, and increasing job opportunities. However,there needs to be better attention to environmental aspects, human resource development and innovation to ensure the sustainability of sustainable tourism development and have a positive impact on local communities.